Fuzzy BIBO Stability of Linear Control Systems - T. Allahviranloo; M. Ayatollahi; F. Amini; E. Vaseghi (Journal of Mathematical Extension, 2014)
In this paper, the concept of stability for fuzzy control systems is discussed from a mathematical point of view. Our main objective is to investigate the stability of fuzzy linear systems with bounded input and bounded output. Necessary and sufficient conditions for this kind of stability are presented by a theorem and it is illustrated by solving an example